Hepatic Organoid-Based High-Content Imaging Boosts Evaluation of Stereoisomerism-Dependent Hepatotoxicity of Stilbenes in Herbal Medicines - Liu, Juan; Li, Tingting; Li, Ruihong; Wang, Jie; Li, Pengyan; Niu, Ming; Zhang, Le; Li, Chunyu; Wang, Tao; Xiao, Xiaohe; Wang, Jia-bo; Wang, Yunfang (Frontiers in Pharmacology, 2022)
The complexity of chemical components of herbal medicines often causes great barriers to toxicity researches. In our previous study, we have found the critical divergent hepatotoxic potential of a pair of stilbene isomers in a famous traditional Chinese herb, Polygonum multiﬂorum (Heshouwu in Chinese). However, the high throughput in vitro evaluation for such stereoisomerism-dependent hepatotoxicity is a critically challenge. In this study, we used a hepatic organoids-based in vitro hepatotoxic evaluation system combined with using high content imaging to differentiate in vivo organ hepatotoxicity of the 2,3,5,4'-tetrahydroxy trans-stilbene-2-O-β-glucoside (trans-SG) and its cis-isomer (cis-SG). By using such organoids platform, we successfully differentiated the two stereoisomers’ hepatotoxic potentials, which were accordance with their differences in rodents and humans. The lesion mechanism of the toxic isomer (cis-SG) was further found as the mitochondrial injury by high content imaging; and its hepatotoxicity could be dose-depended inhibited by the mitochondrial protective agent. These results demonstrated the utility of organoids-based high content imaging approach in evaluating and predicting organ toxicity of natural products by a low cost and high throughput way. It also suggested the rationale to use long-term cultured organoids as alternative toxicology platform to early and cautiously identify hepatotoxic new drug candidates in preclinical phase.